Demonstration of the Effectiveness of Augmented Reality Telesurgery in Complex Hand Reconstruction in Gaza. Issue 3 (March 2018) - Greenfield, Max J.; Luck, Joshua; Billingsley, Michael L.; Heyes, Richard; Smith, Oliver J.; Mosahebi, Afshin; Khoussa, Abu; Abu-Sittah, Ghassan; Hachach-Haram, Nadine
Abstract : Summary: Augmented reality (AR) is defined as "a technology that superimposes a computer-generated image on a user's view of the real world, thus providing a composite view."1 This case report describes how emerging AR telesurgery technologies may be used to facilitate international surgeon–surgeon collaboration and training. Here, we illustrate how a remote surgeon in Beirut, Lebanon, was able to offer assistance to a surgeon in Gaza, Palestine, during a complex hand reconstruction case following a bomb-blast injury in an 18-year-old male. We discuss the implications of AR technology on the future of global surgery and how it may be used to reduce structural inequities in access to safe surgical care.